The Concept of Education in the Qur'an, Surah Al-Alaq, and its Relevance to Contemporary Education - Fatimatul Asroriah; Ndaru Putri Yudhiarti; Imam Shodiq Anshori (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
The article discusses the concept of education found in the Qur'an, specifically in Surah Al-Alaq, and its relevance to the contemporary education context. Surah Al-Alaq is one of the early chapters revealed to Prophet Muhammad SAW, emphasizing the importance of knowledge and learning in Islamic teachings. By analyzing key verses in Surah Al-Alaq, we can understand the fundamental principles of education emphasized in Islam. Surah Al-Alaq begins with the words "Iqra," which means "read." This signifies the importance of reading, writing, and acquiring knowledge in Islamic teachings. In this context, the article reviews the concept of education in Surah Al-Alaq and relates it to contemporary educational principles. The findings of this research conclude that the verses highlight the concepts of reading, creation, and teaching as integral parts of education in Islam. These concepts are highly relevant to contemporary education, which emphasizes literacy, understanding of sciences, and moral education. Surah Al-Alaq also emphasizes that knowledge should be acquired with sincerity and obedience to God. In the context of modern education, these principles can be applied by developing a holistic curriculum that encompasses academic, moral, and spiritual aspects. Learning centered on Islamic values can also help shape students' characters and prepare them to be responsible members of society.Based on this research, the researcher provides recommendations to education practitioners to explore the wisdom and guidance from the Qur'an in shaping a better contemporary education system. Integrating Islamic values with modern educational principles can help create an empowering educational environment and guide learners to become knowledgeable and morally upright individuals.